Hepatoprotective effect of Misopates orontium in rats (Bangladesh Journal of Pharmacology, 2020)
This study explores the hepatoprotective and in vivo antioxidant activities of Misopates orontium. Toxicity studies were conducted on human red blood cells and DNA. Initially, acute hepatoprotective study was done on Wistar rats by giving crude, aqueous, n-hexane, chloroform, ethyl acetate and n-butanol fractions 200 mg/kg/day for 24 hours. Liver function tests were performed. The ethyl acetate fraction was selected for 14 days study. Hepatotoxicity induced by paracetamol (350 mg/kg) orally. All the liver function tests, liver peroxidation tests i.e malondialdehyde, glutathione and histopathological study of the liver was performed at the end of study. In hepatoprotective studies, ethyl acetate fraction showed a significant decrease in the level of serum enzymes (97.6 IU/L), (101 IU/L), (145.17 IU/L) and (0.68 mg/dL). Peroxidation levels in liver homogenates of ethyl acetate-treated group decreased in malondialdehyde (42.5) while reduced glutathione level increased (106.5 nmol/g). This study shows that M. orontium has hepatoprotective and antioxidant effects.